2022
DOI: 10.4103/aja202161
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-activated cell sorting of nonapoptotic spermatozoa with a high DNA fragmentation index improves the live birth rate and decreases transfer cycles of IVF/ICSI

Abstract: The present study aimed to evaluate the clinical outcomes of magnetic-activated cell sorting (MACS) in sperm preparation for male subjects with a sperm DNA fragmentation index (DFI) ≥30%. A total of 86 patients who had undergone their first long-term long protocol were selected. The protocol involved in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles, and the patients were divided into the MACS or control groups. The MACS group included sperm samples analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…, 2022 ). In contrast, in a prospective cohort study, including 80 males with DFI ≥30%, no difference in CPR was found with the use of MACS ( Mei etal. , 2022 ).…”
Section: Resultsmentioning
confidence: 88%
“…, 2022 ). In contrast, in a prospective cohort study, including 80 males with DFI ≥30%, no difference in CPR was found with the use of MACS ( Mei etal. , 2022 ).…”
Section: Resultsmentioning
confidence: 88%
“…Ziarati et al [73] showed increased number of superior embryos and clinical pregnancies when performing DGC + MACS than DGC alone in a study of 80 infertile couples suffering from male factor [73]. In the study by Mei et al [74], selection of nonapoptotic spermatozoa by MACS for higher sperm DFI was found to improve the live birth rate and decrease transfer cycles of IVF/ICSI [74]. Our study suggests that DGC + MACS can be performed before freezing for infertile males suffering from low-quality sperm to optimize the outcomes of ICSI.…”
Section: Discussionmentioning
confidence: 98%
“…During sperm preparation, MACS is a procedure that separates spermatozoa with externalized PS utilizing annexin V-conjugated microbead technology [ 12 ]. The sensitivity of the sperm to DNA fragmentation can also demonstrate the lack of a DNA repair mechanism.…”
Section: Discussionmentioning
confidence: 99%